Tobacco Consumption in Santiago de Chile During the Late Colonial and Early Republican Era [Consumo de Tabaco en Santiago de Chile Durante el Periodo Tardío Colonial E Inicios de la Era Republicana] - Martinez-Barraza, J (Universidad de Murcia, 2018)
This article assesses the consumption of tobacco in Santiago de Chile from the last third of the eighteenth century until the first decades of the republican era. Evidence indicates a rather favourable standard of living in Bourbon America, in contrast with the less optimistic view portrayed by Allen, Murphy and Schneider (2012). The methodology employed here consisted of compiling the trading values of the tobacconist profession, including prices and volumes of tobacco sales, in order to visualize the effective consumption of the population through the use of documentary sources from the Chilean general tobacco administration. The results show that tobacco consumption increased in Santiago during this extended period, in line with population growth and despite the rise in the average price of tobacco. In terms of volume, legal consumption of tobacco exceeded 3 pounds per capita per year at the end of the colonial period, while in the early republican decades it dropped to 2 pounds. This evolution can be explained due to the transformation of the consumption patter n in Santiago, where the colonial preference for less elaborated tobacco gave way to a greater assortment of refined products after the revolutionary period that began in 1810. More importantly, access to tobacco would have been universal, since on average it cost only 2.5% of the annual income of the least qualified workers. © 2018 SEHA.